Thrombotic microangiopathy in cancer. Issue 164 (April 2018) - Weitz, Ilene Ceil
Abstract: Thrombotic microangiopathy (TMA) is clinical syndrome based on the presence of thrombocytopenia (platelet count <150 K or a reduction of the platelet count by >30% from baseline) accompanied by fragmentation hemolysis (MAHA) and evidence of organ damage. It can be seen in a variety of disorders including thrombotic thrombocytopenic purpura (TTP), atypical hemolytic uremic syndrome (aHUS), shigatoxin related hemolytic uremic syndrome (STEC-HUS). Cancer itself has long been associated with both macro and microvascular thrombosis. In addition, treatment with chemotherapy as well as hematopoetic stem cell transplantation (HCST) has been associated with atypical hemolytic uremic (aHUS) like syndrome. In this review, I will discuss the pathophysiology of TMA in cancer, chemotherapy associated HUS, and HSCT, well as new therapeutic interventions. Highlights: Thrombotic microangiopathy (TMA) may occur as a consequence of malignancy, chemotherapy, and hematopoetic transplantation (HSCT). HSCT TMA (TA-TMA) may be associated with calcineurin inhibitors or preparatory drug effects on endothelium. TA-TMA may be associated with underlying complement regulatory protein mutations and is responsive to complement inhibition.